A simplified history of western philosophy : Vol 1: Ancient and medieval philosophy - Omorogbe, Joseph (Lagos, Nigeria : Joja Education Research and Publishers, 1991)
An introduction to the history of ancient and medieval philosophy which provides a clear simplified and summary exposition of the ideas of the major philosophers within the period covered by the book.
Includes bibliographical references.
oif 05/11/14
Loan
Keywords: Philisophy -- History; Philosophy, Ancient; Philosophy, Medieval